Arap gramerinde gayr-i munsarif - General, Ökkeş (My University, 2013)
Arap Gramerinde Gayr-i Munsarif: Gayr-i munsarif, sarftan men edilmiş isim için kullanılan bir kavramdır. Sarftan kasıt ise tenvîndir. Araplar, isimlik hususunda kökleşmiş ve kuvvet kazanmış kelimeler için hafiflik alameti olarak tenvîn kullanırlar. Bu açıdan, isimlikten uzaklaşarak fiillere benzeyen kelimeler, ağır kabul edilir ve tenvînden men edilir. Fiil, isimden türediği için onun fer’i sayılır. Gayr-i munsarif isimler de diğer bazı isimlerin fer’i olması açısından fiile benzerler ve bu sebeple sarftan men edilirler. Gayr-i munsarif isimler, fiile benzemesine sebep olan iki illetle veya iki illet kuvvetindeki bir illetle tenvînden men edilirler. Sarf, tenvîn, munsarif, gayr-i munsarif, sarftan men, fer’, illet, fiile benzeme.

Gayr-i Munsarif in Arabic Grammar Gayr-i munsarif is a concept used for noun which was prohibited from sarf. What wemeanby sarf is tanvin. Arab suse tanvin as a sign of light ness for words being rooted and for cefull for tag (noun). From point of this view, words like verbs is accepted as heavy things by moving away from tag (noun) and is prohibited from tanvin. It is accepted as fer’i of it, since it derives from noun. Also nouns relating. Gayr-i Munsarif likes verb in order to be fer’i of other some nouns and in this regard it is prohibited from sarf. Nouns relating to Gayr-i munsarif is prohibited from tanvin by two illat or an illat in role of two illat. Key Words: Sarf, tanvîn, munsarif, gayr-i munsarif, prohibition from sarf, fer’, illat, likening to verb.
Keywords: Arap Dili; İslam